2019
DOI: 10.3390/cryst9020095
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on Carrier and Exciton Self-Trapping in Strontium Titanate: Understanding the Luminescence Emissions

Abstract: An up-to-date review on recent results for self-trapping of free electrons and holes, as well as excitons, in strontium titanate (STO), which gives rise to small polarons and self-trapped excitons (STEs) is presented. Special attention is paid to the role of carrier and exciton self-trapping on the luminescence emissions under a variety of excitation sources with special emphasis on experiments with laser pulses and energetic ion-beams. In spite of the extensive research effort, a definitive identification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 62 publications
1
31
0
Order By: Relevance
“…Note that the PL peak position is consistent with the red illumination band caused by oxygen vacancies in STO film. [ 38 ] These results validate our model for describing the photodetection behavior of the MoTe 2 /a‐STO heterostructure.…”
Section: Figuresupporting
confidence: 73%
“…Note that the PL peak position is consistent with the red illumination band caused by oxygen vacancies in STO film. [ 38 ] These results validate our model for describing the photodetection behavior of the MoTe 2 /a‐STO heterostructure.…”
Section: Figuresupporting
confidence: 73%
“…A large fraction of the recent reports on oxide perovskites is related to SrTiO 3 [28], where the recent experimental and theoretical information has improved our understanding of the structure and behavior of oxygen vacancies. They are considered to be responsible for some outstanding properties of SrTiO 3 such as an insulating metal transition, superconductive behavior, and photocatalytic properties [3,47].…”
Section: Oxygen Vacancy Centers In Cubic Srtio 3 Under High-energy Ion Beam Irradiation: Real-time Luminescence Emissionsmentioning
confidence: 99%
“…However, the generation, identification, and characterization of the defect centers is a difficult subject and involves a complex set of challenges that has been a matter of controversy. A number of works have been dealing with oxygen vacancy models [15][16][17][18][19][20][21][22][23][24][25][26][27][28]. A large variety of experimental techniques have been used to generate and investigate oxygen vacancy centers.…”
Section: Introductionmentioning
confidence: 99%
“…Pontes et al further found that amorphous thin films show an intense room temperature photoluminescence peak, that is absent for crystalline films. A more detailed overview of several of the mentioned photoluminescence effects is given by Crespillo et al [123]. In addition to the studies presented here, literature is also available for a variety of further doping materials, structural modifications and treatment techniques, used to alter the photoluminescence behaviour of STO.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%